Third‐Person Self‐Talk Reduces Ebola Worry and Risk Perception by Enhancing Rational Thinking. Issue 3 (24th November 2017) - Kross, Ethan; Vickers, Brian D.; Orvell, Ariana; Gainsburg, Izzy; Moran, Tim P.; Boyer, Margaret; Jonides, John; Moser, Jason; Ayduk, Ozlem
Abstract : Background: During the fall of 2014, the threat of an Ebola outbreak gripped the United States (Poll, 8–12 October 2014; see Harvard School of Public Health & SSRS, 2014), creating a unique opportunity to advance basic knowledge concerning how emotion regulation works in consequential contexts and translate existing research in this area to inform public health and policy. Method: We addressed these issues by examining whether third‐person self‐talk, a simple technique that promotes emotion regulation, could nudge people into reasoning about Ebola more rationally. In all, 1, 257 people from across the United States were asked to write about their feelings about Ebola using their name or I (i.e. third‐person self‐talk vs. first‐person self‐talk) as concerns about Ebola swelled (24 October 2014–26 October 2014). Results: Third‐person self‐talk led participants who scored high on Ebola worry at baseline to generate more fact‐based reasons not to worry about Ebola, which predicted reductions in their Ebola worry and risk perception. These findings held when controlling for several theoretically relevant covariates, highlighting their robustness. Conclusion: These results demonstrate how a simple linguistic technique can enhance rational thinking and quell worry about a pressing public health threat.